2012
DOI: 10.1007/s00264-012-1699-y
|View full text |Cite
|
Sign up to set email alerts
|

Shape of growth plate of proximal femur in children and its significance in the aetiology of slipped capital femoral epiphysis

Abstract: PurposeThe main objective of the study was to present the influence of the morphological shape of the proximal femoral growth plate in children as one of the risk factors for the incidence of slipped capital femoral epiphysis (SCFE) in adolescents.MethodsThis research is based on the X-ray, computed tomography (CT) and magnetic resonance imaging (MRI) data obtained for 100 children three to 13 years old, all treated at the Children’s Orthopaedic Clinic and Rehabilitation Department and Department of Radiology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 17 publications
1
33
0
Order By: Relevance
“…Our results offer insight into decision making for in situ pinning or adapting corrective osteotomies in cases of poor remodelling. Additionally, Kandzierski et al reported that a growth plate finally reaches a shape of a convex meniscus and that minor ruggedness of its surface gradually disappears at the age of 11-13 years [22]. These growth-plate changes might indicate poor remodelling ability after the age of 11 years.…”
Section: Discussionmentioning
confidence: 99%
“…Our results offer insight into decision making for in situ pinning or adapting corrective osteotomies in cases of poor remodelling. Additionally, Kandzierski et al reported that a growth plate finally reaches a shape of a convex meniscus and that minor ruggedness of its surface gradually disappears at the age of 11-13 years [22]. These growth-plate changes might indicate poor remodelling ability after the age of 11 years.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed a significant difference in the contralateral PSA between the SCFE and control groups, and 70 % of contralateral hips in the SCFE group had increased posterior inclination compared to the mean PSA + 2SD in the control group. These morphological changes might contribute to future impingement and degenerative joint disease [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Observations made by Kandzierski et al [14] show that the growth plate of a 13-year-old child has a form of a part of a sphere. This means that curvature exists in both coronal and sagittal planes.…”
Section: Geometrical Modelmentioning
confidence: 97%
“…This means that curvature exists in both coronal and sagittal planes. However, for an 11-year-old child, physeal morphology resembles a meniscus; that is, it has the shape of a curved disc [14]. Therefore, physeal curvature in all cases was modeled only in the coronal plane.…”
Section: Geometrical Modelmentioning
confidence: 99%
See 1 more Smart Citation